Influence of Glucose, Urea and Bacteria Concentration On Nata De Cassava Preparation Using Liquid Tapioca Waste Medium - Muhammad Ghozali; Yenny Meliana; Witta Kartika Restu; Evi Triwulandari; Mochamad Chalid (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2022)
In this research, Nata de Cassava as the obtained bacterial cellulose was synthesized by Acetobacter xylinum using the liquid tapioca waste as the media. This research aimed to investigate the influence of concentration from carbon and nitrogen sources and then the type of bacteria used toward the obtained Nata de Cassava. The liquid tapioca waste was heated in a beaker glass at 70-80 °C and then added 5-10 % (w/v) of sugar and 0.1-0.5 % (w/v) of urea. The mixed solution was poured into a container and then cooled. Furthermore, 10-20 % (v/v) of Acetobacter xylinum was added and incubated at room temperature. After ten days, the Nata de cassava was harvested, sterilized, and immersed in ethanol, then dried in an oven at 60 °C. The results of FTIR, XRD and SEM analysis showed that Nata de Cassava had been successfully synthesized. The composition that produced the highest Nata de Cassava yield of 2.41% was the composition using 15% of A. xylinum, 10% of glucose and 0.1% of urea in the fermentation medium. In addition, the composition that produced the highest carbon conversion ratio of 26.15% was the composition that used 10% of A. xylinum, 5% of glucose and 0.2% of urea in the fermentation medium.